(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article deals with the basics of assessing specially protected natural areas. A specially protected natural area is an important element in the development of a "green" economy. Because specially protected areas not only maintain a natural balance, but also serve as a source of normal life for people. The article considers various ways of assessing specially protected natural areas. With the help of ecological and economic evaluation of specially protected natural areas, their values are increased. However, for this assessment there are a number of obstacles. In particular, some elements of specially protected natural areas need to be assessed not only economically, but also their spiritual value. And spiritual values can not be measured economically. The article also highlights key indicators of the effectiveness of specially protected natural areas.